PrimPol‐mediated repriming facilitates replication traverse of DNA interstrand crosslinks. (15th June 2021) - González‐Acosta, Daniel; Blanco‐Romero, Elena; Ubieto‐Capella, Patricia; Mutreja, Karun; Míguez, Samuel; Llanos, Susana; García, Fernando; Muñoz, Javier; Blanco, Luis; Lopes, Massimo; Méndez, Juan
Abstract: DNA interstrand crosslinks (ICLs) induced by endogenous aldehydes or chemotherapeutic agents interfere with essential processes such as replication and transcription. ICL recognition and repair by the Fanconi Anemia pathway require the formation of an X‐shaped DNA structure that may arise from convergence of two replication forks at the crosslink or traversing of the lesion by a single replication fork. Here, we report that ICL traverse strictly requires DNA repriming events downstream of the lesion, which are carried out by PrimPol, the second primase‐polymerase identified in mammalian cells after Polα/Primase. The recruitment of PrimPol to the vicinity of ICLs depends on its interaction with RPA, but not on FANCM translocase or the BLM/TOP3A/RMI1‐2 (BTR) complex that also participate in ICL traverse. Genetic ablation of PRIMPOL makes cells more dependent on the fork convergence mechanism to initiate ICL repair, and PRIMPOL KO cells and mice display hypersensitivity to ICL‐inducing drugs. These results open the possibility of targeting PrimPol activity to enhance the efficacy of chemotherapy based on DNA crosslinking agents. SYNOPSIS: Recognition and repair of DNA interstrand crosslinks (ICLs) caused by aldehydes or chemotherapeutics is crucial to prevent interference with replication. Human PrimPol, a primase involved in DNA damage tolerance, promotes replicative "traverse" of ICLs, facilitating continuous DNA synthesis and post‐replicative repair of ICL lesions by the Fanconi Anemia (FA) pathway. PrimPol is recruited to ICLs through its interaction with RPA. PrimPol promotes replicative traverse of ICLs, creating a suitable template for FA proteins involved in ICL repair. The function of PrimPol at ICLs is epistatic with FANCM and the BTR (BLM‐Top3A‐RMI1‐RMI2) complex, but not with NEIL3 glycosylase. Genetic ablation of PrimPol sensitizes cells and mice to DNA‐crosslinking agents. In the absence of PrimPol, cells rely on alternative pathways such as fork convergence to initiate ICL repair. Abstract : A specialized human primase involved in DNA damage tolerance facilitates continuous DNA synthesis past ICL lesions, and their post‐replicative repair via the Fanconi Anemia pathway.